Free-Standing Pb(Zr, Ti)O3 Thick-Films Prepared By a One-Step Air Co-Firing Technique - Kok, Swee Leong; White, Neil; Nick, Harris (2008)
Combinations of conventional thick-film technology and sacrificial layer techniques were used to fabricate free-standing structures, in the form of cantilever beams. By taking advantage of the different thermal expansion coefficients between silver/palladium (Ag/Pd) and piezoceramic Pb(Zr, Ti)O3, it was possible to fabricate a flat, but angled cantilever. In this work, sandwich structures consisting of PZT layers and Ag/Pd conductors, with in either interdigitated (IDT) or plated electrode configurations were fabricated in order to investigate the structural strength and the characteristics of free-standing structures. Screen printed carbon was used as a sacrificial layer. In the final step of the process, this was burnt out at a temperature of 850 C in an air environment. This resulted in a free-standing, sandwich structure of PZT-Ag/Pd. In order to reduce the problems of process complexity, a one-step firing process was used, whereby the sacrificial layer was co-fired together with PZT-Ag/Pd layers. The measurement results showed that the materials have a piezoelectric charge coefficient, d31 of -25 pC/N and coupling coefficient, k31 of 0.125. The cantilever structures were found to have a maximum Q-factor of around 200, and produced useful amounts of electrical power when driving resistive loads at low acceleration levels.